Determinants Of Msmes Welfare Through Sharia Financial Literacy In Ultra-Micro Financing - Hasan, Asyari; Nasution, Siti Sarah; Nasution, Hairatunnisah; Arafah, Santi (Integrated Journal of Business and Economics (IJBE), 2024)
This research aims to determine how much influence sharia financial inclusion, financial experience and financial management have on the welfare of MSMEs through sharia financial literacy at PT. Pegadaian Syariah Langsa. This research uses a quantitative approach using 88 MSME actors who are registered in Ultra Micro financing. Based on cross section data using analysis techniques in the form of SEM-PLS. The results of the research analysis conducted with 5% alpha show that  sharia financial literacy moderates by strengthening the relationship between sharia financial inclusion and sharia financial experience on the welfare of MSMEs, while sharia financial literacy neither strengthens nor weakens the relationship between financial management and the welfare of MSMEs. The welfare of MSMEs is based on a good and increasing condition of productive businesses owned by individuals and / or individual business entities that have micro business criteria must be based on an understanding of sharia financial literacy, because sharia financial literacy is a fundamental factor for economic growth and financial stability in sharia